Nurses’ Perceptions of Electronic Health Record Usability in Obstetrics and Gynecology - Zeynep OĞUL (Applied Medical Informatics)
Background: Implementation of Electronic Health Records (EHRs) is recommended to enhance patient care quality. Nurses play a crucial role as key users in the successful adoption of EHR systems. Purpose: This study aimed to explore the perceptions of nurses working in obstetrics and gynecology regarding the usability of an EHR system. Method: A descriptive, quantitative, and cross-sectional design was used. Cluster random sampling was applied to obtain a representative sample from hospitals across the six regions of Northern Cyprus. Data were collected in 2022. One main health center from each region was selected to ensure representativeness. Data were collected using the Turkish version of Brooke's 1996 scale, translated by Demirkol and Şeneler, to assess the usability of EHRs. The data were used to evaluate nurses’ usability of the EHR system. Results: The participants were predominantly young, female, bachelor’s degree holders, and mainly employed in public hospitals with limited job experience. EHRs are mostly used for tracking lab results and patient care planning. The primary benefits were time savings and easier access to information. Conclusion: Nurses perceive that EHRs can reduce unnecessary workloads and improve patient care quality.